“A thowsond mylys a sonder”: Catholic exiles from Tudor England and the ambiguities of loneliness - Smith, FE (Palgrave Macmillan, 2025)
Recent research on early modern exile has emphasised the remarkable ability of émigrés to maintain dynamic connections with their former homes whilst also forging new connections abroad. Although offering an important corrective to older studies which tended to assume that exiles formed isolated, inward-looking groups abroad, this research has nonetheless diverted attention away from the more emotional impacts of displacement. This chapter aims therefore to provide a deeper exploration of the “loneliness” of early modern exile. Focusing on the letters and writings of English Catholics who fled their homeland in opposition to the religious policies of Henry VIII and Edward VI, it argues that, despite maintaining connections with loved ones back home and being accepted into their new communities abroad, these émigrés still struggled with feelings we might term “loneliness.” They employed a specific vocabulary centring on “separation” and “solitude” to express these emotions, and indeed there were some important differences between the ways these émigrés described their feelings and modern understandings of loneliness. Nevertheless, this chapter ultimately suggests that such differences should not prevent us from recognising that the “loneliness” experienced by these émigrés was every bit as complex and intense as its modern counterpart.